Menggunakan Video Pembelajaran untuk Meningkatkan Pemahaman Isu Global dalam Pendidikan Islam di SMPN 1 Pagerageung - Nasir, Tatang Muh; Yudiyanto, Mohamad; Ruswandi, Uus; Sabarudin, Mohammad; Sugiana, Yusuf (Universitas Pendidikan Ganesha, 2025)
Islamic Religious Education (PAI) faces challenges in aligning learning materials with technological developments and global issues. This study aims to analyze the effectiveness of the use of learning videos in improving students' understanding of global issues. The research method used was a quantitative survey with a questionnaire involving 33 students in grades IX H and IX J. Data were collected through a closed questionnaire with a Likert scale as well as interviews with teachers to gain in-depth insights about the implementation of learning videos. Data analysis was carried out in a quantitative descriptive manner with percentages, as well as qualitative analysis to understand teachers' perceptions of the obstacles and benefits of using technology. The results showed that 96.9% of students found PAI interesting, 75.7% felt that the material was relevant to daily life, but only 36.4% of students stated that teachers often use learning videos. As many as 75.8% of students stated that globalization has an effect on their religious understanding, while 72.7% consider social media to help their understanding of Islam. However, 63.7% of students feel that outside culture can weaken their beliefs. In conclusion, the integration of learning videos in PAI improves student understanding, but its use is still limited. A more systematic strategy is needed, including the selection of relevant content, teacher mentoring, and interactive discussions so that learning is more effective and contextual in the digital era.